Effects of lactate concentration on T‐cell phenotype and mitochondrial respiration - Eunhan Cho; Guillaume Spielmann; Brian A. Irving (Physiological Reports)
Abstract Lactate is a critical regulator of cellular processes and immune signaling, and we hypothesize that exercise‐induced elevations in lactate help activate immune cells in response to vigorous exercise. Despite its importance, the impact of lactate on T‐cell mitochondrial respiration remains poorly understood. This study examines the impact of exposure to physiologically relevant lactate concentrations (0.5 and 4.0 mM) on the mitochondrial respiration of resting T‐cells. Resting T‐cells were isolated from 12 healthy participants (mean ± SD, 26.8 ± 3.5 years) and cultured in a plasma‐like medium with either 0.5 mM (control) or 4 mM lactate for 1 h to mimic resting and vigorous exercise conditions. The composition of T‐cell subsets was characterized using flow cytometry, and mitochondrial respiration was measured using high‐resolution respirometry. Exposure to 4 mM lactate significantly increased mitochondrial oxygen flow (IO2, pmols∙s−1 million T‐cells−1) across all respiratory states compared to the control condition (0.5 mM) (all p < 0.01), suggesting an enhanced capacity for oxidative phosphorylation compared to the control. This study demonstrates that lactate preconditions T‐cells and leads to enhanced mitochondrial respiration, offering insights into immune cell metabolism under exercise‐like conditions, independent of exercise‐induced differential mobilization of immune cell subsets.